The Dialogue with Islam - Salenson, Christian (Cistercian studies quarterly, 2012)
The article focuses on the necessity of a dialogue between the Christians and the Muslims. According to Pope John Paul II, he sees the urgency of a dialogue, particularly, when Christians and Muslims have come to a phase of history to acknowledge and develop the spiritual bonds which unite the two religious sectors. Also, it mentions that the dialogue with Islam is based from the declaration Nostra Aetate of the Vatican Council II which points that the Church has a high respect for Muslims.